Navigating the barriers: an in-depth exploration of how personal protective equipment influences the relational dynamics between healthcare workers and patients - Bertuol, Maria; Barello, Serena; Casella, Giovanna; Dibennardo, Federico; Acampora, Marta; Buscella, Angelica; Mancini, Jessica; Bertuzzi, Elena; Sarli, Leopoldo; Bonacaro, Antonio; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: This study explores the communication dynamics between healthcare professionals and patients amidst the mandatory use of personal protective equipment (PPE) during the Covid-19 pandemic. It specifically examines the strategies employed by healthcare professionals to address communication barriers posed by these protective instruments. Methods: A qualitative approach was taken using semi-structured interviews. With participants’ consent, interviews were recorded, transcribed verbatim, and analyzed thematically. Results: Thirteen qualitative semi-structured interviews were conducted with a diverse group of professionals in medical and critical care settings in northern Italy. Thematic analysis unveiled three key themes: (1) The influence of Personal Protective Equipment (PPE) on the healthcare worker-patient relationship, (2) Strategies and tools for improving patient communication, and (3) Key takeaways and lessons learned. Conclusions: The COVID-19 pandemic catalyzed a transformation in global healthcare communication dynamics. Despite the challenges posed by PPE usage, healthcare professionals displayed remarkable resilience, creativity, and unwavering dedication to patient care. The unique circumstances of the COVID-19 pandemic make it a valuable observatory for drawing lessons applicable to contexts where PPE remains a necessity. The challenges faced during this period provide insights into how healthcare professionals adapted their communication methods to ensure effective and empathetic patient interaction despite the physical barriers introduced by PPE. By scrutinizing the experiences and strategies employed in this extraordinary context, this study seeks to contribute to a broader understanding of effective communication in healthcare settings that require ongoing PPE usage